Pengembangan Aplikasi Web Smart Waste Management Berbasis IoT dan Dashboard Spasial Untuk Optimasi Rute Pengangkutan Sampah - Muhammad Ammar Fariz Baihaqi; Kurniawan Dwi Irianto (Journal of Information System Research (JOSH), 2026)
Increasing urban waste creates logistical hurdles for the Sleman Waste Services (UPTD). Static collection schedules without actual capacity data lead to operational inefficiencies. This study designs an Internet of Things (IoT)-based Smart Waste Management system integrated with a spatial dashboard to optimize collection efficiency. System development adopted the Waterfall method, encompassing hardware (ESP32 and HC-SR04) and web interfaces. Telemetry transmission utilizes a REST API for real-time visualization. Test results indicated a sensor accuracy of 97.2% with an average network latency of 7.46 seconds. User Acceptance Test (UAT) and black-box tests recorded success rates exceeding 95%. Operationally, the smart routing implementation successfully reduced the daily fleet travel distance from 25 km to 12 km (52% fuel efficiency). The main contribution is twofold. Scientifically, it proposes an integrated architecture combining IoT telemetry and spatial smart routing within a single platform. Practically, the system is proven to reduce fleet travel distance and achieve 52% fuel savings, providing an effective solution to prevent waste overload and realize efficient urban sanitation logistics.